Efect of alstonia angustiloba tree moisture absorption on the stabilization of unsaturated residual soil slope - Muhammad Syamsul Imran, Zaini; Muzamir, Hasan (Springer Berlin Heidelberg, 2024)
In this study, the investigation on the influence of Alstonia Angustiloba tree moisture absorption at various depths and separation on the development of persuaded moisture absorption in soil were performed. The slope stabilization analysis were conducted considering two conditions (dry and wet conditions) at two different slope (saturated and unsaturated slope). Besides, the tree moisture absorption data generated during the course of 8 months of on-site monitoring are recorded and applied to assess the safety factor of the slope. Slope stabilization analysis is then performed and represented in two-dimensional and three-dimensional contour model to investigate the effect of plant transpiration on the slope stabilization. According to the findings, at the slope crest with the existence of Alstonia Angustiloba tree, the tree moisture absorption recorded a maximum value, at a distance and depth of 1.1 and 0.25 m. Moreover, the findings also proved that larger tree moisture absorption enhanced the slope's safety factor by up to 53% (from 2.17 to 4.57). The tree moisture absorption can provide an environmentally benign technique that can be used globally to avert slope disaster.